The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.24043/isj.56
|View full text |Cite
|
Sign up to set email alerts
|

Small island perspectives on climate change

Abstract: Islands and islanders are often misrepresented in the climate change discourse, oversimplifying their experiences and interactions with climate change. In reality, islands and islanders have far more complex relationships with climate change. This special thematic section presents eight papers that highlight local responses and localized impacts of climate change on islands, reiterating the importance of considering local community perspectives in small island contexts to overcome simplistic viewpoints. Such p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…A significant new focus in climate change research as a whole surrounds questions about risk perceptions. Climate change is projected to play a role in altering risk patterns on a global scale both by enhancing the impacts and intensity of long established exposure events as well as creating new patterns of risk exposure for individuals, groups and business enterprises that formerly may not have considered themselves at risk (Dessai & Sims, 2010: Capstick et al, 2015Helm et al, 2018: Walshe & Stancioff, 2018. Climate change based risk perceptions are significant because of the manner in which they represent a subjective element of decision-making processes and as such can stall or constrain vital actions needed to reduce risk (Leiserowitz, 2005).…”
Section: Tourism and Climate Change Perceptionsmentioning
confidence: 99%
“…A significant new focus in climate change research as a whole surrounds questions about risk perceptions. Climate change is projected to play a role in altering risk patterns on a global scale both by enhancing the impacts and intensity of long established exposure events as well as creating new patterns of risk exposure for individuals, groups and business enterprises that formerly may not have considered themselves at risk (Dessai & Sims, 2010: Capstick et al, 2015Helm et al, 2018: Walshe & Stancioff, 2018. Climate change based risk perceptions are significant because of the manner in which they represent a subjective element of decision-making processes and as such can stall or constrain vital actions needed to reduce risk (Leiserowitz, 2005).…”
Section: Tourism and Climate Change Perceptionsmentioning
confidence: 99%
“…In order to tackle this urgent and extremely complex and important task, the first step is to gain a better insight into the influence of recent climate changes, first and foremost global warming processes. It should be noted that each island has different climate changes, which differently influence their landscape and socioeconomic structure (Méheux et al, 2007;Walshe and Stancioff, 2018). This paper examines the temperature and precipitation development in the 1948-2018 period on the island of Lastovo.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the published literature on climate resilience has been concerned about mainland coastal areas throughout the world. However, island communities in Bangladesh are not given sufficient attention [89]. This study reviews some research that uses data from coastal mainlands but found hardly any empirical research or secondary review covering issues of island communities in Bangladesh.…”
Section: Geographical Disparity In the Coverage Of Coastal Island Commentioning
confidence: 98%